1980
DOI: 10.1002/1097-0142(19801101)46:9<2100::aid-cncr2820460932>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal carcinoma in alaskan eskimos, indians, and aleuts: A review of cases and study of epstein-barr virus, HLA, and environmental risk factors

Abstract: The records of thirty-one patients with nasopharyngeal carcinoma (NPC) diagnosed from 1966 through 1976 among the Alaskan native population (Eskimo, Aleut, Indian) were reviewed. There were 25 males and six females, which results in relatively high incidence rates per 100,000 of 13.5 for males and 3.7 for females. Clinical and pathologic features were similar to those found among southern Chinese NPC patients. Five-year survival rate was 48%. Antibodies to Epstein-Barr virus were higher in NPC patients than in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
1

Year Published

1983
1983
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(35 citation statements)
references
References 31 publications
2
32
0
1
Order By: Relevance
“…In studies of Chinese populations, the relative risk of NPC associated with weekly consumption, compared with no or rare consumption, generally ranged from 1.4 to 3.2, whereas that for daily consumption ranged from 1.8 to 7.5 (136)(137)(138)(139)(140)(141). NPC risk is also elevated in association with other preserved food items, including meats, eggs, fruits, and vegetables, in southern Chinese, Southeast Asians, North Africans/Middle Easterners, and Arctic natives (38,39,(138)(139)(140)(141)(142)(143)(144)(145)(146)(147), as well as in low-incidence northern Chinese (148) and the U.S. population (excluding type I NPC; ref. 149).…”
Section: Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…In studies of Chinese populations, the relative risk of NPC associated with weekly consumption, compared with no or rare consumption, generally ranged from 1.4 to 3.2, whereas that for daily consumption ranged from 1.8 to 7.5 (136)(137)(138)(139)(140)(141). NPC risk is also elevated in association with other preserved food items, including meats, eggs, fruits, and vegetables, in southern Chinese, Southeast Asians, North Africans/Middle Easterners, and Arctic natives (38,39,(138)(139)(140)(141)(142)(143)(144)(145)(146)(147), as well as in low-incidence northern Chinese (148) and the U.S. population (excluding type I NPC; ref. 149).…”
Section: Risk Factorsmentioning
confidence: 99%
“…The majority of casecontrol studies examining cigarette smoking and risk of NPC in a variety of populations reported an increased risk of 2-to 6-fold (9,39,40,73,142,(172)(173)(174)(175)(176)(177)(178)(179)(180)(181), establishing tobacco smoke as a consensus risk factor for NPC (182), although some studies found no association (24,38,74,137,141,148,154,(183)(184)(185)(186). Reports of a positive association between domestic exposure to secondhand smoke and risk of NPC (40,146,180) are likewise countered by studies with null findings (39,174).…”
Section: Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that consumption frequency of salt-preserved fish is associated with the risk of NPC. However, elevated NPC risk is also associated with other preserved food items, including meats, eggs, fruits, and vegetables [4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Epidemiology Of Nasopharyngeal Carcinomamentioning
confidence: 99%
“…With 98 cases diagnosed among men and 52 among women, nasopharyngeal cancer accounted for 4.7% of all malignancies during the period, a percentage equal to that of stomach cancer (Table 9). Based on the age-stan- was 1.9:l. Ninety-six percent of all carcinomas were histologically verified (Table 7).…”
Section: Nasopharynx (Icd9 147)mentioning
confidence: 99%